PENGUATAN MANAJEMEN PENINGKATAN MUTU BERBASIS SEKOLAH (MPMBS) MELALUI IMPLEMENTASI KURIKULUM 2013 - Ermi, Sola (Idaarah: Jurnal Manajemen Pendidikan, 2018)
School Based Management is basically giving the freedom for a school to manage all the activities at school in order to reach the goals effectively and efficiently. Office of Educational Research and Improvement (the US Department of Education, in Sutjipto, 2000) defines that School Based Management is a strategi to improve education by transferring significant responsibility from state and district offices to individual schools… provides prinicipals, teachers, students and parents greater control over the education process by giving them responsibility for decision about the budget, personnel, and the curriculum. Curriculum 2013 is aimed at preparing Indonesian citizens. especially students to have qualified life skills as individuals and or citizens who believe in God, productive, creative, innovative, and affective